(untitled) (Research Announcements "Heritage BG", 2025)
The current study focuses on wellness innovations and good aromatherapy practices demonstrated in the digital presentation of 74 spas and 25 wellness centers included in the National Tourist Register. Aromatherapy methods have an important place in the Bulgarian wellness culture. There is a tendency for the development and application of comprehensive rituals and concepts based on aroma-therapeutic effects. The creative approach in the development and presentation of rituals and procedures with the use of essential oils. The natural products and resources are the conditions for making Bulgaria an attractive Wellness destination for Niche tourism. References: Atanasova-Spasova 1962: Atanasova-Spasova, M. Eterichni masla. Sofiya. Cherneva-Georgieva 2017: Cherneva-Georgieva, Dzheni. Bioraznoobrazie i prilozhenie na lekarstvenite rasteniya ot Severno-Chernomorskite vlazhni zoni v etnobotanikata. Varna. Denkova, Denkov 1999: Denkova, Rumyana, Denkov, Veselin. Narachnik po aromototerapiya. Sofiya. Dimitrova et al. 2021: Dimitrova, Bistra, Nikolay Izov, Velichka Alexandrova, Rumen Iosifov, Darinka Ignatova, Dimitar Trendafilov, Vasil Petrov, Gergana Vasileva. Smart kognitiven instrumentarium. Vŭnshna otsenka na profesionalni kompetentsii za kadri v Nishov turizŭm. NSA Press. Sofiya. Fol 2009: Fol, Aleksandar. Trakiyskata kultura. Kazano i premalchano. Sofiya. Ivanov 2018: Ivanov, Ivan. Lechebnite svoystva na rasteniyata. Sofiya. Garnev 2020: Garnev, Nikolay. Kniga na familniya biznes v Balgariya. Sofiya. Petrovski, Stoyanov 2005: Petrovski, Svetoslav, Stoyanov, Stavri. Eterichni masla i prilozhenieto im v meditsinata i promishlenostta. Sofiya. Prodanova-Stefanova 2021: Prodanova-Stefanova Vanya. Izsledvaniya varhu svoystvata na balgarskite eterichni masla. Yambol. Shniter 2001: Shniter, Mariya. Molitva i magiya. Sofiya. Stoyanova, Georgiev, Atanasova 2007: Stoyanova, Albena, Georgiev, Atanasova, Teodora, Rakovodstvo za laboratorni uprazhneniya po Tehnologiya na eterichnite masla, Plovdiv. Dimitrova, Nesheva 2021: Dimitrova, Bistra, Nesheva, Irina. Research to Improve Health Care for Women with Normal Pregnancy Applying Recreational Wellness Activity. Trakia Journal of Sciences. Supplement, Vol. 19, 684-690. Donev et al. 2019: Donev Jordan, Stoyan Andonov, Stefka Djobova, Jordan Jordanov Donev, Oleg Hristov, Ivelina Kirilova, Stoyan Bahchevanski, Rumen Iossifov, Velichka Aleksandrova, Bogomil Angelov, Natali, Stoyanova. Comparative Study of Measuring Physical Activity among Sport Students. Proceeding book, 369-374.